Plan de negocios para determinar la viabilidad de la elaboración y comercialización de perfumes líquidos naturales para hombres y mujeres en la ciudad de Quito - Alarcón Aguilar, Byron Patricio (2019)
The distribution and commercialization of perfumes and cosmetics has provided general and direct employment, to more than 500 thousand individuals in Ecuador. A problem continues with the majority brands of perfumes and cosmetics used by Ecuadorians. Theses products come from chemical substance that can be harmful to humans, as well to the environment. It is a very strong impact, especially in the 21 century with so much talk about the destruction and reduction of the ozone layer that protects humans from the ultraviolet rays from the sun. Despite the background of the use on such products and the chemical substances they contain, today people have high standards on beauty and good physical appearance. Wich reflects off hair styles, aromas even what clothes people are wearing. Therefore, there is a high demand for these products that move the economy. It is relevant to offer natural perfumes to the population of Quito. The market study defined that the entrance barriers are high, in such a way that the difference is mainly in the quality, using natural essential oils and elaborating them in an artisanal way; but with the best quality, guaranteed, because each product manufactured meets the legal requirements of the market and the preferences of consumers. The financial analysis determined the amount to be invested, with which the business starts. The results are favorable, which shows that the project is profitable, viable and feasible, the return of the project is greater than the average cost of capital required by the shareholder. This analysis and financial evaluation, and also of the market to cover or cover, shows that the shareholders will recover and multiply the money invested very soon, because they will start offering natural perfumes to the inhabitants that make up the economically active population of the Metropolitan District of Quito, and then, as the elaboration, commercialization and distribution of the merchandise grows, it is intended to be commercialized in the main cities of Ecuador.